Anesthesia Management of Patients with Redo Craniotomy: Cases of Supratentorial Recidive Tumors - Bisri, Dewi Yulianti; Septiani, Gusti Ayu Pitria; Limawan, Michaela Arshanty; Bisri, Tatang (Interdisciplinary Social Studies, 2023)
Background: Compared to non-surgical therapies, redo craniotomy is linked to improved neurological state and a lower mortality rate. But it also carries a higher price tag and complication risk. Aim: The researchers would like to discover anesthesia management of patients with redo craniotomy in patients with supratentorial recidive tumors. Method: The researchers used the case study method. Two cases of redo craniotomy performed at the Santosa Hospital Bandung Central Indonesia are presented. The first case involved a 24-year-old male with a supraorbital tumor, GCS 15, and the second case involved a 43-year-old woman with  meningiomas, GCS 15. The first patient underwent redo craniotomy six (6) months after the first operation, while the second patient underwent the procedure three (3) months after the first operation. These patients were subjected to anesthesia using the same techniques and anesthetic drugs. patients were positioned in a neutral position with 20-30 degree head up, voluntary hyperventilated, and adequate anxiolytics. Findings: The bleeding volume of the patients was 800 mL for the first patient and 1,000 mL for the second, and the fluid balance was maintained using the ringerfundin balance solution. The durations of the operation of the first and second patients were  4 and 6.5 hours, respectively. Postoperatively, patients were treated in the ICU for one day under mechanical ventilation and were transferred to the ward after extubation. Better intraoperative care, improved surgical skills, surgical equipment, and better intensive care support are likely to improve outcomes in patients with redo craniotomy.